Analysis of the Impact of Parents Leaving Children for Family Harmony in Islamic Law - Padhil, Muhammad; Muchtar, M. Ilham; Muntadzar, Ahmad (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2024)
One of the obligations of parents to their children is to be an educator to grow and develop their children. The problem is, both parents who work and are busy to take care of and educate children, then take steps to entrust their children. The main problems of this study are divided into 2 main problems, namely: 1. How is the law to entrust children according to Islamic law? 2. What is the impact of entrusting children on harmony in the family? This research uses a type of library research (Library Research) with analysis of juridical-normative method research methods. The sources of this research data are the Qur'an, hadith, books of salaf (former) and khalaf (contemporary) scholars, and journals related to the subject matter. Furthermore, the method of data collection by reading books and scientific papers, studying, translating, and analyzing data related to the subject matter. Then draw conclusions. The results of this study show that the law delegates care by entrusting it to daycare, or babysitter, or to the child's grandparents, depending on the reason for the busy life of parents (especially the mother). If the reason is because of looking for wealth to help the family economy, it is permissible with the conditions that have been prepared by Fukaha. As for if the reason is because of pursuing a career, then in terms of benefit, it is not allowed especially if there is no time with family. There are several positive and negative impacts of entrusting children to family harmony. The negative effects are; Children who are less close to their parents, children will become closed, parents also miss important moments with their children, children's mindsets will be different, lack of religious education, and not awakened akhlak karimah (good ethics). The positive effects are; The task of parents will be helped in the midst of their busy lives, socialization and communication of children increases, and parenting is more experienced.